2022
DOI: 10.1002/lno.12096
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of microcystin production and biodegradation rates in the western basin of Lake Erie

Abstract: Cyanobacterial biomass forecasts currently cannot predict the concentrations of microcystin, one of the most ubiquitous cyanotoxins that threaten human and wildlife health globally. Mechanistic insights into how microcystin production and biodegradation by heterotrophic bacteria change spatially and throughout the bloom season can aid in toxin concentration forecasts. We quantified microcystin production and biodegradation during two growth seasons in two western Lake Erie sites with different physicochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…The stimulation of additional growth, which was indicated by changes in chl-a in several of the experiments, did not link to shifts in pMC levels except for short-lived, small increases in IR and CP. In line with the findings from other MC production studies, cellular resources may have been diverted away from MC production and toward growth due to limiting conditions further explaining a lack of pMC production during later time points [32].…”
Section: Shifts In Microcystin Concentration and Partitioningsupporting
confidence: 86%
See 2 more Smart Citations
“…The stimulation of additional growth, which was indicated by changes in chl-a in several of the experiments, did not link to shifts in pMC levels except for short-lived, small increases in IR and CP. In line with the findings from other MC production studies, cellular resources may have been diverted away from MC production and toward growth due to limiting conditions further explaining a lack of pMC production during later time points [32].…”
Section: Shifts In Microcystin Concentration and Partitioningsupporting
confidence: 86%
“…Finally, the importance of potential MC-degrading bacteria as proxies for bloom stage and toxicity have been discussed previously in relation to pMC release [ 26 , 32 , 36 ]. While no community data were collected to characterize any shifts in the assemblages during the incubation trials, the initial characterization of the bloom-associated bacteria using high-throughput sequencing highlighted different relative contributions from taxa that have been associated with MC degradation and also indicated that Microcystis was the dominant toxin-producing genus upon bloom collections [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These two sites were selected for experimentation due to differing water quality, but both being prone to cyanobacterial blooms. Complete methods for these experiments are presented in Chaffin et al (2022) . Briefly, there were four nutrient enrichment treatments: (1) no enrichment control, (2) phosphate and nitrate, (3) phosphate and ammonium, and (4) phosphate and urea.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, some of these cyanolytic bacteria have the potential to degrade cyanotoxins such as MCs and suppress blooms instantaneously (Li et al, 2016). Consequently, considerable attention has been paid to heterotrophic bacteria in freshwater due to their potential as agents to control or terminate the excessive growth of cyanobacteria (Van Le et al, 2022; Wang et al, 2020; Zhang et al, 2019) and to degrade cyanotoxins (Chaffin et al, 2022; Idroos & Manage, 2018; Nájera et al, 2017). Although the identification of an effective biological control agent is challenging, recognizing and isolating bacteria with the ability to lyse Microcystis sp.…”
Section: Introductionmentioning
confidence: 99%